Skin manifestations of connective tissue diseases in childhood. 2. Dermatomyositis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
In our pediatric cases dermatomyositis is as fequent as lupus erythematosus. Lupus erythematosus mainly affects peripuberal age and, in some cases, the newborn period. On the other hand, dermatomyositis may affect any age with an average age of 6 years in our pediatric cases. Both sexes are affected at this age without significant differences, whereas adult females are more frequently affected. Skin manifestations are more monomorphous in dermatomyositis as compared with lupus and scleroderma. In contrast with these connective tissue diseases, in dermatomyositis lesions are almost always symmetrical. Juvenile dermatomyositis is never paraneoplastic, in contrast with the adult form. Calcinosis is no fequent in our cases, without significant difference between children and adults. Vasculitic manifestations are slightly more frequent in children. They manifest themselves as microinfarcts of the fingertips, petechias and telangiectasias of the eyelids. In the latter site the vasculitic manifestations may lead to small atrophic scars. Steroid are not indicated in all the cases. Non steroid anti-inflammatory drugs may be effective in cases with only minimal skin lesions.